Penurunan Persentase Kecacatan di PT Injaplast - Tanzil, Carolin -; Bendatu, Liem Yenny (Jurnal Titra, 2015)
PT Injaplast is one of the manufacturing company that produces weaving plastic bags (sacks). PT Injaplast had received customersâ complaint related to its quality, which are tear apart, sacks were broken, logo werenât centered, sloping cutting, and miscolors. DMAIC (define, measure, analyze, improve and control) is one of the methods that are used to fix the problem. This final project is using cause and effect diagram as a tool to find the root cause of the problem. The proposed improvements are optimalizing the reject sacks with trial and error, using aid instruments, using work instruction, placing poster, maintenance scheduling, string addition, and additonal task to the operator. Quality plan is also given to improve the quality control. Implementation is performed on some of the proposed improvements which are placing poster on putting thread at creel, adding working instruction on loom process and using reject sacks. The result of this implementation showed that the defect percentage after cutting sacks is reduced by 0,39% and the defect percentage after the sacks have been printed is reduced by 0,25%.